How many long‐stay schizophrenia patients can be discharged in Japan? - OSHIMA, IWAO; MINO, YOSHIO; INOMATA, YOSHIMASA (Psychiatry and clinical neurosciences, 2007)
The mental health‐care system in Japan remains hospital‐based, and has the largest number of psychiatric beds per capita in the world. However, serious discussion about deinstitutionalization has recently begun. This study attempts to determine the proportion of inpatients that would benefit from community‐based programs, as judged by hospital psychiatrists, and to evaluate the need for community resources for their community placement. Inpatients with schizophrenia from 139 hospitals were randomly selected. Data on the psychiatrists’ judgment of discharge and required resources for community placement were obtained for 2758 subjects. Among the subjects, 1097 (39.8%) were judged to have the possibility of being discharged using community resources (possible discharge group; PDG). Provided that the proportion of PDG was 40%, controlling for the hospital background variables, the number of schizophrenia inpatients with a hospital stay of ≥1 year who could be discharged from psychiatric hospitals in Japan was estimated to be 66 000. For the PDG, the required community resources, including accommodation, daytime activity, and daily living support services, were calculated. The numbers of governmental targets for community resources, including community accommodation, daytime activities, and daily living support services may have been underestimated.